The Influence of Implementating Performance Allowence Policies and Leadership On Employee Performance at RSUD Haji Makassar - Ikram M, Muhaidir; Haerani, Sitti; Ismail, Muhammad (Economics and Business Journal (ECBIS), 2023)
The primary objective of this study is to investigate the impact of the implementation of performance allowance policies and leadership on employee performance within the context of Haji Makassar General Hospital. The quantitative research methodology aims to elucidate the causal relationship between the variables under examination. The population under investigation consisted of 67 employees of Haji Makassar General Hospital, and the entire population was included as the sample for this study. The data collection techniques included questionnaires, documentation analysis, interviews, and an extensive literature review. The data analysis methodology contained multiple regression analysis and hypothesis testing in partial and simultaneous manners. The research findings indicate that the variables of performance allowance policies and leadership engagement exhibit a positive and significant influence on employee performance at Haji Makassar General Hospital. In other words, the research hypothesi.